Hubungan Pemberian Vaksin Campak Dengan Kejadian Pneumonia Dan Diare Pada Balita Di Indonesia - Risnasari, Annisa; Azhary R N, Muhammad (Journals of Ners Community, 2023)
Background: Childhood is the child's most vulnerable to various types of diseases, such as pneumonia and diarrhea. Pneumonia and diarrhea are the main killers in children aged 12-59 months, both of these diseases are also complications or secondary infections from measles. According to Global Action Plan WHO 2013 one of the strategies to reduce the morbidity and mortality of pneumonia and diarrhea in infants is measles vaccination. Objective: To know the correlation of measles vaccine with the incidence of pneumonia and diarrhea in infants in Indonesia. Method: This research uses quantitative research with a cross-sectional study design. This study took secondary data obtained from the Indonesian Family Life Survey (IFLS) wave 5 of 2014. The method of sampling used total sampling, the samples obtained were 3124 people. Data obtained were analyzed using chi-square. Result: In the chi-square correlation test the correlation of measles vaccine with the incidence of pneumonia and diarrhea, obtained p-value of (0.210). Conclusion: There is no correlation between measles vaccine and pneumonia and diarrhea in children under five in Indonesia.